Relationship Management in Tourism Microenterprises as an Element in Building a Competitive Advantage - Maciej Debski; Michał Szaniawski (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
Tourism is central to the growth of numerous regions across the world, including Poland. A substantial part of infrastructure designed to serve tourists is created by microenterprises. These entities possess limited human or financial resources, and this translates into reduced possibilities for applying diverse competitiveness instruments. It seems that an attractive concept recommended to be pursued for their growth is relationship marketing. For the purposes of this paper, the authors conducted consumer research using the PAPI method and a series of interviews within the companies discussed. The results obtained helped to positively verify the hypothesis presuming that microenterprises enjoy substantial potentials for establishing relationships, though these potentials are not fully used. Moreover, the findings from the consumer research revealed the factors pivotal in delivering tourist satisfaction, which is then an essential requirement for developing positive relationships.